Wanted dead & alive - Mthembu-Salter, Gregory (Face2Face, 2019)
"Given what we know about climate change, should we still be raising and eating cattle? And how do we weigh the cultural and economic value of cattle against their environmental impact? This engaging book brings history, science, economics and popular culture together in a timely discussion about whether current practices can be justified in a period of rapid climate change. Journalist Gregory Mthembu-Salter first encountered South Africa's love of cattle during his own lobola negotiations. The book traces his personal journey through kraals, rangelands and feedlots across South Africa to find out more about the national hunger for cattle. He takes a broad sweep - drawing on such diverse sources as politicians involved in land reform, history, braai-side interviews with cattle farmers and abattoir owners, conversations with his mother-in-law, and analysis of cutting-edge science. Mthembu-Salter suggests that perhaps 'cattle can remain wanted and treasured ... more as living assets, kept in modest numbers on land where crops will not thrive, whose beef is eaten rarely - and, when it is, is savoured.'"--Publisher⁰'s description
Keywords: Cattle / Breeding / South Africa; Cattle / Climatic factors; South Africa; cattle; meat; dairy farms; ranches; Cattle / Breeding